Application of Sujok Therapy on Pain And Blood Pressure in Hypertension Patients - Suryana, Rika; Rasyid, Muhamad Amirul; Nurjannah, Intansari; Harjanto, Dwi (Universitas Padjadjaran, 2024)
Pain in hypertensive patients can worsen the patient's blood pressure. Sujok therapy is one of the suitable therapies used to reduce the pain scale. This activity aims to describe how the effect and application of Sujok therapy on pain scale and blood pressure in hypertensive patients. This activity included physical assessment, psychosomatic symptoms, disease history, pain scale and the provision of Sujok therapy to 19 hypertension elderly. This activity was carried out for two days on November 21, 2023 at Prolanis Puskesmas Jetis II Bantul, Yogyakarta and on November 26, 2023 at the Baiturrahman Mosque Popongan, Yogyakarta. Sujok therapy is carried out using methods such as massage with probes, fenugreek seeds attachment, and chakra magnet attachment to the hand which is the basic correspondence system and insect correspondence system. The test used to see pain comparison was paired sample t-test and to compare blood pressure was Wilcoxon test. The results of the assessment found various physical complaints, namely headaches, neck and shoulder pain, lower and upper extremity pain, and back and waist pain. After therapy, there was a significant decrease in pain scale (p=0.000) and systolic blood pressure (p=0.004) in hypertensive patients. This activity shows that Sujok therapy with the method of massaging the probe tool, fenugreek seeds, and magnetic attachment to the basic correspondence system and insect correspondence system can be an alternative therapy to reduce pain and blood pressure in hypertensive patients.Keywords: Hypertension, pain, sujok therapy.